A Comprehensive Study Of Sandhi Sharir In Ayurveda With Special Reference To The Applied Anatomy Of The Knee Joint - Kumar, Mahesh; Priyanka, Priyanka; Gupta, S. S. (Journal of Neonatal Surgery, 2025)
Sandhi Sharir, as described in Ayurveda, refers to the anatomical and functional junctions where two or more bones meet, ensuring mobility, stability, and coordinated body movements. These structures are sustained by the balanced function of doshas, dhatus, and upadhatus, particularly the role of Shleshaka Kapha in lubrication and smooth articulation. Among all Sandhis, the Janu Sandhi (knee joint) holds paramount importance due to its role in weight-bearing, locomotion, and postural stability. Classical Ayurvedic texts such as Charaka Samhita, Sushruta Samhita, and Ashtanga Hridaya detail its structural composition, functional attributes, and its classification as a marma (vital point), underlining its clinical significance in trauma and degenerative conditions.In modern anatomy, the knee joint is recognized as the largest synovial hinge joint, comprising femoro-tibial and femoro-patellar articulations, stabilized by ligaments, menisci, muscles, and a synovial capsule. This review correlates Ayurvedic and biomedical perspectives of Janu Sandhi, exploring the synergy between traditional descriptions and contemporary anatomical and biomechanical insights. It also discusses common pathologies such as osteoarthritis, ligament injuries, and inflammatory disorders, alongside preventive and therapeutic approaches from both disciplines. Ayurvedic interventions, including abhyanga (therapeutic oil massage), swedana (sudation), vasti (medicated enema), and rasayana therapy, are examined in light of their potential to maintain joint health and improve functional outcomes. By integrating classical concepts with modern applied anatomy, this review highlights the scope for interdisciplinary management strategies in knee joint disorders